Hubungan Profesionalisme Guru dengan Hasil Belajar Siswa di SMPN 1 Nanggung Bogor - Muhammad Rofi; Chaira Sadiah; Yusi Prihartini (EduInovasi: Journal of Basic Educational Studies, 2021)
In the learning process, student learning outcomes can relate to the professionalism of the teacher. This study aims to determine the level of professionalism of class VIII Islamic education teachers at SMPN 1 Nanggung, to determine the level of PAI learning outcomes of grade VIII students of SMPN 1 Nanggung and to determine the professionalism relationship between teachers of slamic education and learning outcomes of grade VIII students of SMPN 1 Nanggung. This research is a quantitative descriptive study with the X1 variable being the professionalism of the teacher, the X2 variable being the PAI teacher professionalism and the Y variable being the Student Learning Outcomes. The number of students was 76 out of 260 students. Data were collected using documentation and questionnaire methods. The validity of the questionnaire instrument was carried out by analyzing the items using the Product Moment correlation formula and the reliability test using the Cronbach Alpha formula. The results showed that: there is a positive and significant relationship between the professionalism of the PAI subject teachers and the learning outcomes of the VIII grade students of SMPN 1 Nanggung, a correlation coefficient of 0.242 with a sig value of 0.019 means that there is a significant positive relationship between teacher professionalism and student learning outcomes. The strong relationship between professionalism and learning outcomes is in the low category. Thus the test shows "there is a significant relationship between the professionalism of Islamic education teachers with the learning outcomes of grade VIII students of SMPN 1 Nanggung with a low category.